HYDROGEOCHEMISTRY OF THE PERMAFROST ZONE IN THE CENTRAL PART OF THE YAKUTIAN DIAMOND-BEARING PROVINCE, RUSSIA - Alexeev S.V.; Alexeeva L.P. (My University, 2003)
The hydrogeochemical characteristics and zonation of the permafrost zone in the central part of the Yakutian diamond-bearing province formed mainly under the influence of cryogenic processes that occurred in the late Cenozoic. On the basis of field and experimental studies, conclusions were formulated that the perennial cryogenesis of the sedimentary cover in this region resulted in increasing the concentration of carbonate and sulfate compounds in groundwaters as well as increasing the concentration of easily soluble compounds (sodium, magnesium, and calcium chlorides).